2021
DOI: 10.3389/fbioe.2021.642671
|View full text |Cite
|
Sign up to set email alerts
|

Automated Online Flow Cytometry Advances Microalgal Ecosystem Management as in situ, High-Temporal Resolution Monitoring Tool

Abstract: Microalgae are emerging as a next-generation biotechnological production system in the pharmaceutical, biofuel, and food domain. The economization of microalgal biorefineries remains a main target, where culture contamination and prokaryotic upsurge are main bottlenecks to impair culture stability, reproducibility, and consequently productivity. Automated online flow cytometry (FCM) is gaining momentum as bioprocess optimization tool, as it allows for spatial and temporal landscaping, real-time investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…These developments are supported by data analysis pipelines (e.g. Rubbens & Props, 2021), enabling online and also real‐time evaluations (Favere et al, 2020; Haberkorn et al, 2021). Among the reviewed articles focused on soil, the analyses of community structures based on cytometric fingerprinting, considering both gate and bin methods, have been reported for microbial photoautotroph (Menyhárt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These developments are supported by data analysis pipelines (e.g. Rubbens & Props, 2021), enabling online and also real‐time evaluations (Favere et al, 2020; Haberkorn et al, 2021). Among the reviewed articles focused on soil, the analyses of community structures based on cytometric fingerprinting, considering both gate and bin methods, have been reported for microbial photoautotroph (Menyhárt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in microbial community analysis from machine learning of FCM data have also been reported (Özel Duygan & van der Meer, 2022). These technological advancements enable automated data acquisition and analysis prompting research on microbial biodiversity (De Vrieze et al, 2021; Haberkorn et al, 2021; Özel Duygan & van der Meer, 2022; Pereira et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modular approach and proper analysis would allow to identify and reject any running reactor that might not fulfil the requirements for human consumption. Automated flow cytometry with advanced data analysis relying on phenotypic fingerprinting could contribute to a continuous monitoring of the microbial community (Haberkorn et al, 2021). The use of flow cytometry in a known non-axenic culture can enable the understanding of population dynamics and their response to external events.…”
Section: Non-axenic Cultivationmentioning
confidence: 99%
“…Well-known examples are SYBR Green I (Ex 497 nm/Em 520 nm), DAPI (Ex 358 nm/Em 461 nm), PicoGreen (Ex 480 nm/Em 520 nm) and SYTO 9 (Ex 483 nm/Em 503 nm), which are extensively used due to their good membrane permeability and their compatibility with almost all bench-top flow cytometers [ 4 , 12 , 15 , 16 , 17 , 36 , 37 , 38 , 39 ]. However, a review of the current literature revealed a wide range of discrepancies in staining methods, with varying results and limited comparability [ 21 , 22 , 23 , 26 , 27 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], highlighting the need for standardized, reproducible protocols. Moreover, only a small number of protocols give an explanation of why staining parameters such as dye concentration, staining time and temperature were chosen, or how stable the added fluorochromes were [ 16 ].…”
Section: Introductionmentioning
confidence: 99%